2013
DOI: 10.1016/j.jss.2013.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of PTEN activity decreases metastases in an orthotopic model of colon cancer

Abstract: Background Mutational loss of tumor suppressor phosphatase and tensin homologue deleted on chromosome ten (PTEN) is associated with malignant progression in many cancers including colorectal cancer (CRC). PTEN is involved in negatively regulating the Phosphatidylinositol 3-kinase (PI3K)/AKT oncogenic signaling pathway and has been implicated in the metastatic colonization process. Few in vivo models are available to study CRC metastasis. The purpose of this study was to determine the effect of restoring PTEN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Loss of PTEN was positively correlated with malignant progression of CRC (15), restoration of PTEN reduced the ratio of metastases of CRC (16). Current study aimed to investigate whether there were miRNAs that targeted PTEN and regulated the progression of CRC, thus providing a therapeutic target for CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of PTEN was positively correlated with malignant progression of CRC (15), restoration of PTEN reduced the ratio of metastases of CRC (16). Current study aimed to investigate whether there were miRNAs that targeted PTEN and regulated the progression of CRC, thus providing a therapeutic target for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences demonstrated the involvement of PTEN deactivation in tumorigenesis, whose loss increased the activity of PI3K/AKT and was correlated with cell proliferation, migration, invasion and apoptosis (13,14). Moreover, another study showed that PTEN, whose loss was positively correlated with malignant progression including tumor size and TNM advanced stage, played a crucial role at early/late stages of CRC (15); meanwhile, restoration of PTEN was reported to reduce the ratio of metastases in an orthotopic model of CRC (16). Current study aimed to investigate whether there are miRNAs that could target PTEN and regulate the progression of CRC, thus providing a therapeutic target for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies performed in in vivo model systems show that PTEN reactivation in a colorectal cancer (CRC) cell line exhibiting PTEN loss reduces its metastatic capability without affecting primary tumor formation. Moreover, PTEN reactivation also changed the organotropic homing from liver and lung metastasis to liver-only metastasis ( 182 ). Importantly, Razis et al have shown that PTEN levels are predictive of cetuximab efficacy in CRC models with activated EGFR signaling and wild type KRAS/BRAF status and in the presence of an intact PI3K/AKT pathway ( 48 ).…”
Section: Pten Loss In Human Cancermentioning
confidence: 99%
“…In 1987 was created an orthotopic model of CRC in mice with injection of tumor cells in the ceacum, which enabled the study of local tumor invasion as well as metastatic dissemination—it was a more patient‐like animal tumor model . The success of this model was very high, turning it into a valuable asset in the study of the CRC, and amply used, with even some adaptations as injection of tumor cells in the rectum, and even exploring microvascular patterns of the colon concerning the differences between the mesenteric and antimesenteric side…”
Section: What Type Of Crc Models Exist?mentioning
confidence: 99%